From scale to substance: how green credit policy execution and “purity” reshape regional innovation - Yang, Shuangquan (Frontiers in Environmental Science, 2025)
IntroductionChina’s green credit system has expanded dramatically, yet substantial heterogeneity in local policy implementation raises questions about its effectiveness in spurring environmental innovation. This paper introduces the novel concept of “Green Credit Purity”—the proportion of green credit flowing to genuinely environmental projects—to examine how policy implementation intensity and allocation quality jointly determine innovation outcomes.MethodsUsing panel data covering 1,600 firms across 280 prefecture-level cities from 2010–2022, we employ fixed effects, spatial Durbin models, and instrumental variables to establish causal relationships.ResultsWe find that a one-standard-deviation increase in local Green Credit Policy Implementation Intensity (GCPI) generates a 2.1% increase in firm-level green patents and 3.3 percentage points improvement in regional Green Total Factor Productivity. Crucially, firms with high credit purity achieve 68% larger innovation responses than those engaging in “greenwashing.” Spatial analysis reveals positive spillovers equivalent to 40% of direct effects, while threshold regression identifies a critical point (GCPI = 0.416) beyond which policy stringency triggers firm relocation.DiscussionThese findings demonstrate that green credit effectiveness depends critically on both implementation intensity and allocation quality, with implications for designing environmental finance policies that balance local stringency with regional coordination to maximize genuine innovation while minimizing regulatory arbitrage.